2015
DOI: 10.1002/ase.1582
|View full text |Cite
|
Sign up to set email alerts
|

How the distinctive cultures of osteopathic and allopathic medical schools affect the careers, perceptions, and institutional efforts of their anatomy faculties: A qualitative case study of two schools

Abstract: Anatomy faculties are integral to basic science instruction in medical schools, particularly given the preponderance of anatomic instruction in the preclinical curriculum. Recent years have witnessed major curricular restructuring and other emerging national trends that pose significant challenges to anatomists. An examination of anatomy faculty perceptions at two philosophically distinct medical schools within this shifting climate provides an indicator of how different institutional characteristics may impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…In the context of completion of PLAs, there is universal consensus that the provision of choice to students in learning methods is a strong motivator of IM. 43 Hence, considering the preferences of current generation of healthcare students 7,41 it is suggested that the completion of PLAs should be voluntary, though students should be encouraged to complete PLAs on schedule. Therefore, PLAs can provide an autonomy-supportive environment of students that can enhance their intellectual meta-levels of thinking.…”
Section: Extent Of Use Of Prelaboratory Assignments (Plas) By Studentsmentioning
confidence: 99%
“…In the context of completion of PLAs, there is universal consensus that the provision of choice to students in learning methods is a strong motivator of IM. 43 Hence, considering the preferences of current generation of healthcare students 7,41 it is suggested that the completion of PLAs should be voluntary, though students should be encouraged to complete PLAs on schedule. Therefore, PLAs can provide an autonomy-supportive environment of students that can enhance their intellectual meta-levels of thinking.…”
Section: Extent Of Use Of Prelaboratory Assignments (Plas) By Studentsmentioning
confidence: 99%
“…In the context of completion of PLAs, there is universal consensus that the provision of choice to students in learning methods is a strong motivator of IM. 43 Hence, considering the preferences of current generation of healthcare students 7,41 it is suggested that the completion of PLAs should be voluntary, though students should be encouraged to complete PLAs on schedule. Therefore, PLAs can provide an autonomy-supportive environment of students that can enhance their intellectual meta-levels of thinking.…”
Section: Extent Of Use Of Prelaboratory Assignments (Plas) By Studentsmentioning
confidence: 99%
“…Despite a lack of concrete evidence, it is thought that interprofessional collaboration improves patient outcomes by enhancing communication and increasing accessibility to services [ 1 3 ]. Numerous studies evaluating collaborative practice/education have been published, but studies to date have largely overlooked collaboration between allopathic (MD) and osteopathic (DO) physicians [ 4 ].…”
Section: Introductionmentioning
confidence: 99%